2022
DOI: 10.1128/spectrum.01219-22
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis of SARS-CoV-2 Genomes and Correlations among Highly Prevalent Mutations

Abstract: We performed a meta-analysis on SARS-CoV-2 genomes categorized by collection month and identified several significant mutations. Pearson correlation analysis of these significant mutations identified 16 comutations having absolute correlation coefficients of >0.4 and a frequency of >30% in the genomes used in this study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…On the other hand, the study of Kim et al MicroScale Thermophoresis analysis revealed that the NSP12 P323L mutation stabilized the NSP12-NSP7-NSP8 complex interaction [ 37 ]. Periwal et al also suggesetd that the P323L had a stabilizing effect relative to the wild type protein [ 61 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the study of Kim et al MicroScale Thermophoresis analysis revealed that the NSP12 P323L mutation stabilized the NSP12-NSP7-NSP8 complex interaction [ 37 ]. Periwal et al also suggesetd that the P323L had a stabilizing effect relative to the wild type protein [ 61 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Although the F106F mutation was considered silent, it was associated with an altered miR-197-5p target sequence, a host-specific miRNA necessary to defend against coronaviruses [ 48 ]. Studies have demonstrated a strong correlation between these non-structural protein mutations and the spike mutation, indicating a potential interaction that could impact viral pathogenesis and evolution [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…While substitutions within SARS-CoV-2 may act at a structural level to stabilize RNA structure ( 25 ) or viral proteins such as NSP12 ( 26 ), these may also facilitate protein-protein interactions both between viral proteins and with host proteins. Several studies have investigated the cellular interactome of the SARS-CoV-2 proteome including NSP12 [e.g., reference ( 15 )].…”
Section: Discussionmentioning
confidence: 99%